2020
DOI: 10.3748/wjg.v26.i41.6378
|View full text |Cite
|
Sign up to set email alerts
|

Associations of content and gene polymorphism of macrophage inhibitory factor-1 and chronic hepatitis C virus infection

Abstract: BACKGROUND The expression of macrophage inhibitory factor-1 (MIC-1) is increased in peripheral blood of patients with chronic hepatitis and liver cirrhosis. However, whether MIC-1 gene polymorphism is correlated with relevant diseases is not yet reported. AIM To explore the correlation between gene polymorphism in MIC-1 exon region and chronic hepatitis C virus (HCV) infection. METHODS Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…G to C mutation suggested higher risk of SLE, which may lead to increased GDF-15 mRNA expression, and increased serum levels of GDF-15 in SLE patients. Rs1059519 was located at exon, which has been reported to associate with GDF-15 expression and relate to chronic hepatitis C infection, left ventricular hypertrophy (20)(21)(22). In our study, rs1059519 polymorphism was related to SLE risk and SLE complicated with discoid and pleurisy, suggesting that rs1059519 may regulate vascular injury and inflammation.…”
Section: Discussionsupporting
confidence: 54%
“…G to C mutation suggested higher risk of SLE, which may lead to increased GDF-15 mRNA expression, and increased serum levels of GDF-15 in SLE patients. Rs1059519 was located at exon, which has been reported to associate with GDF-15 expression and relate to chronic hepatitis C infection, left ventricular hypertrophy (20)(21)(22). In our study, rs1059519 polymorphism was related to SLE risk and SLE complicated with discoid and pleurisy, suggesting that rs1059519 may regulate vascular injury and inflammation.…”
Section: Discussionsupporting
confidence: 54%
“…In this study, we also found that in the dominant model, people carrying rs1059519 C allele had lower FPG levels, indicating that people carrying G allele were more likely to have elevated FPG and HbA1c levels. Previous study has shown that the polymorphism of rs1059519 was correlated with the level of plasma MIC-1 (GDF-15), and the level of MIC-1 in GG genotype was significantly higher than that in CC genotype [ 30 ]. A study of hypertensive patients in China found that rs1059519 G allele have significantly increased plasma levels of GDF-15 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found the genotype and allele frequency distribution at the rs1059519 locus, not for rs1059369, significant differed between the patients and healthy controls. The genotype GG at the rs1059519 locus follow with high content of AST, PIIINP, MIC-1 were suggested as independent relevant factors for CHC [ 40 ]. In the current study, the genotype and allele frequency of the two sites did not differ significantly between the responsive and non-responsive groups and between the SVR and non-SVR groups ( P > 0.05).…”
Section: Discussionmentioning
confidence: 99%